2009
DOI: 10.1039/b822528a
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor compounds from actinomycetes: from gene clusters to new derivatives by combinatorial biosynthesis

Abstract: Covering: up to October 2008. Antitumor compounds produced by actinomycetes and novel derivatives generated by combinatorial biosynthesis are reviewed (with 318 references cited.) The different structural groups for which the relevant gene clusters have been isolated and characterized are reviewed, with a description of the strategies used for the generation of the novel derivatives and the activities of these compounds against tumor cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 299 publications
3
93
0
1
Order By: Relevance
“…Many of these secondary metabolites are potent antibiotics, which has made streptomycetes the primary antibiotic-producing organisms exploited by the pharmaceutical industry [2] . Members of this group are producers, in addition, of clinically useful antitumor drugs such as anthracyclines (aclarubicin, daunomycin and doxorubicin), peptides (bleomycin and actinomycin D), aureolic acids (mithramycin), enediynes (neocarzinostatin), antimetabolites (pentostatin), carzinophilin, mitomycins and others [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…Many of these secondary metabolites are potent antibiotics, which has made streptomycetes the primary antibiotic-producing organisms exploited by the pharmaceutical industry [2] . Members of this group are producers, in addition, of clinically useful antitumor drugs such as anthracyclines (aclarubicin, daunomycin and doxorubicin), peptides (bleomycin and actinomycin D), aureolic acids (mithramycin), enediynes (neocarzinostatin), antimetabolites (pentostatin), carzinophilin, mitomycins and others [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…While there are several reports about the control of secondary metabolite production by actinobacteria [12,13] , optimization of cultivation conditions is expected to improve the secondary metabolite production. In this study, optimization of pigment production by the strain of Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] In particular, a great effort has been made in the study of polyketide antitumor drugs to generate novel derivatives and to improve their production yields by combinatorial biosynthesis approaches. [19][20][21][22] The research shown below and developed in our laboratory at the University Institute of Oncology from Principado de Asturias (IUOPA) represent my modest contribution to the research on polyketide during the period 2000-2010.…”
Section: Keeping On Polyketide Biosynthesismentioning
confidence: 99%